Response and remission criteria in major depression - a validation of current practice - Riedel, Michael; Möller, Hans-Jürgen; Obermeier, Michael; Schennach-Wolff, Rebecca; Bauer, Michael; Adli, Mazda; Kronmüller, Klaus-Thomas; Nickel, Thomas; Brieger, Peter; Laux, Gerd; Bender, Wolfram; Heuser, Isabella; et al. (Journal of psychiatric research, 2010)
Remission and response were suggested as the most relevant outcome criteria for the treatment of depression. There is still marked uncertainty as to what cut-offs should be used on current depression rating scales. The goal of the present study was to compare the validity of different HAMD, MADRS and BDI cut-offs for response and remission. The naturalistic prospective study was performed in 12 psychiatric hospitals in Germany. All evaluable patients (n=846) were hospitalized and had to meet DSM-IV criteria for major depressive disorder. Biweekly ratings were assessed using HAMD-21, MADRS and BDI. A CGI-S score of 1 and a CGI-I score of at least 2 was used as the primary comparative measure of remission and response, respectively. A HAMD-21 cut-off≤7 (AUC: 0.92), HAMD-17 cut-of≤6 (AUC: 0.90), MADRS cut-off≤7 (AUC: 0.94) and BDI cut-off≤12 (AUC: 0.83) were associated with a maximum of specificity and sensitivity for defining remission. A minimum decrease of 47% of the HAMD-21 (AUC: 0.90), ≤57% for HAMD-17 (AUC: 0.89), ≤ 46% for MADRS (0.91) and a decrease of 47% for the BDI baseline score (AUC: 0.78) best corresponded CGI response criteria. Our data largely confirmed currently used remission and response criteria in naturalistically treated patients.
Gesehen am 15.05.2023